Implementasi Metode Ruqyah Dalam Mengatasi Problem Rumah Tangga Di Jam’iyyah Ruqyah Aswaja Sidoarjo - Anwar , Choirul (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to understand the implementation of the ruqyah method in addressing household problems at Jam’iyyah Ruqyah Aswaja (JRA) Sidoarjo, its impact on marital relationships, as well as the supporting and inhibiting factors of its implementation. Using a descriptive approach, the study found that the ruqyah method, which involves the recitation of Qur'anic verses, helps improve strained marital relationships. Patients reported improvements in physical conditions, such as relief from headaches, heavy shoulders, and excessive emotional outbursts after undergoing the ruqyah process. They also felt more motivated to improve themselves and became more diligent in worship. Supporting factors for the implementation of the ruqyah method include public awareness of the Qur'an's function as a medium for healing, the dissemination of information through social media, and the simplicity of the method, making it accessible to everyone. Inhibiting factors include public perceptions that ruqyah is solely for non-medical complaints, fears of reactions such as possession during the process, and the view of ruqyah as merely an alternative treatment. This study highlights the potential of the Qur'an-based ruqyah method as a holistic solution for household problems, connecting spiritual aspects with emotional well-being, while also opening opportunities for further research on integrating spirituality into family conflict resolution.